Upward Planarization Layout - Chimani, Markus; Gutwenger, Carsten; Mutzel, Petra; Wong, Hoi-Ming (Journal of Graph Algorithms and Applications, 2011)
Recently, we presented a new practical method for upward crossing minimization [], which clearly outperformed existing approaches for drawing hierarchical graphs in that respect. The outcome of this method is an upward planar representation (UPR), a planarly embedded graph in which crossings are represented by dummy vertices. However, straight-forward approaches for drawing such UPRs lead to quite unsatisfactory results. In this paper, we present a new algorithm for drawing UPRs that greatly improves the layout quality, leading to good hierarchal drawings with few crossings. We analyze its performance on well-known benchmark graphs and compare it with alternative approaches. <!—->